(untitled) (Bangladesh Journal of Animal Science, 2015)
The experiment was conducted at Bajar Para bathan of Shajadpur upazila under Sirajgonj district to study the effects of intercropping on high yielding fodder production in Bathan areas of Sirajgonj district. In this experiment, fodders were cultivated in 27 experimental plots of each size (15×15m) were arranged in 9 treatments as Khesari (Sole), Napier dwarf early, Napier dwarf late, Splendida, Jumboo, Khesari+Napier dwarf early, Khesari+Napier dwarf late, Khesari+Splendida and Khesari+Jumboo. The biomass yield of Napier dwarf early, Napier dwarf late, Splendida and Jumboo as sole crop were 100.32, 90.26, 72.31 and 48.33 ton/ha., respectively. The yield of Khesari was 58.76 ton/ha. as sole crop and differs significantly (p<0.01) when intercropped with Napier dwarf early, Napier dwarf late, Splendida and Jumbo. The fresh total biomass yield of intercropped high yielding fodders and Khesari was considerably higher (151.11 ton/h) compared to sole high yielding fodders (100.32 ton/h) and sole Khesari (58.76t/h). The total highest biomass yield (151.11 ton/ha.) was obtained from the combination of Napier dwarf early and Khesari intercropping, followed by Napier dwarf late and Khesari (134.63ton/ha.), Splendida and Khesari (115.73 ton/ha.) then Jumboo and Khesari (87.55 ton/ha.), respectively. The total biomass yield difference among the intercropped group was significant (p<0.05). The land equivalent ratio (LER) increased in the intercropped practices of Khesari+Napier dwarf early, Khesari+Napier dwarf late, Khesari+Splendida and Khesari+ Jumboo (1.84, 1.75, 1.73 and 1.65, respectively) compared with sole Napier dwarf early, Napier dwarf late, Splendida, Jumboo and Khesari. Benefit cost ratio (BCR) of Khesari+Napier dwarf early cropping method was 1.73 which was higher than others cropping method. It may be suggested to cultivate Napier dwarf early along with Khesari in the bathan land in the existing feeding system. DOI: http://dx.doi.org/10.3329/bjas.v44i1.23124 Bang. J. Anim. Sci. 2014. 44 (1): 21-25